Rational selection of TbpB variants yields a bivalent vaccine with broad coverage against Neisseria gonorrhoeae - Jamie E. Fegan; Epshita A. Islam; David M. Curran; Dixon Ng; Natalie Y. T. Au; Elissa G. Currie; Joseph J. Zeppa; Jessica Lam; Anthony B. Schryvers; Trevor F. Moraes; Scott D. Gray-Owen (npj Vaccines)
Abstract Neisseria gonorrhoeae is an on-going public health problem due in part to the lack of success with efforts to develop an efficacious vaccine to prevent this sexually transmitted infection. The gonococcal transferrin binding protein B (TbpB) is an attractive candidate vaccine antigen. However, it exhibits high levels of antigenic variability, posing a significant obstacle in evoking a broadly protective immune response. Here, we utilize phylogenetic information to rationally select TbpB variants for inclusion into a gonococcal vaccine and identify two TbpB variants that together elicit a highly cross-reactive antibody response against a diverse panel of TbpB variants and clinically relevant gonococcal strains. This formulation performed well in experimental proxies of real-world usage, including eliciting bactericidal activity against diverse gonococcal strains and decreasing the median duration of colonization after vaginal infection in female mice. These data support the use of a combination of TbpB variants for a broadly protective gonococcal vaccine.